Description of the functional properties of the nociceptive trigeminal system in relation to pulpal pain - Andrés Pérez Ruíz; María Isabel Ventura Hernández; Orietta Valverde Grandal (Editorial Ciencias Médicas, 2015)
Introduction: The nociceptive trigeminal system constitutes a component of the  sensorial system somestetic which has the capacity to discriminate against four basic variables of the stimuli that cause damage tisular, that is to say, its quality, temporary course, localization and intensity. Objective: The conceptual elements to facilitate the understanding Odontology needed for the description the functional properties the trigeminal nociceptive systems, may continuous shown the pain manifestation the transit pulpar inflammatory process. Content: The fibres to joint to nociception are Aδ and C in the dental pulp. This classification the pain, by some criterions: sensation qualities, in relationships the body location, and nociceptor ubication. The evolution in pulpar condition there is classification in: reversible pulpitis, transitional pulpitis, pulpitis irreversible and necrotic pulp.For by quality the pulpar pain have been: Sharp o continues, by your apparition provocate or espontain, by evolution intermittent o continues, by your localization limited by one region, irradiator y refereed, by intensity slight, moderate or severe. Final considerations: We concluded that the importance of prefunding capacity sensorial nociceptive systems in relationships by the way modality, temporal course, localization and intensity the stimulation, you now the divers section in transit the pulpar process inflammatory.